Students’ Lived Experience of Project-Based Learning - Ferianda, Sandy; Mukarto, Fransiscus Xaverius (Beyond Words, 2017)
Inspired by personal experiences during the study time in the Graduate Program in English Language Studies (ELS) Sanata Dharma University Yogyakarta, this research focused mainly on investigating the ELS students’ lived experience of project-based learning implemented by the ELS lecturers. This study employed hermeneutic phenomenology since it described and interpreted the meanings of ELS students lived experience. The participants of this study were the three ELS students considered to be illuminating from the three different streams batch of 2015. In this study we used one-on-one in depth interview to gain the data. The findings of this study consisted of four prefigured meanings and two emergent meanings namely a) authentic learning, b) learner autonomy, c) cooperative learning, d) multiple intelligences, e) understanding others, and f) personal development. The findings of this study gave implications not only to the ELS students and lecturers, but also to the audience. Lastly, recommendations were also addressed to the ELS students as their habit formation, to the ELS lecturers as their inputs to give more feedbacks to their students, and to the future researchers. Keywords: Lived experience, project-based learning.